Empowering Nepal’s Future: Madhesh University’s Role in Harnessing the Demographic Dividend - Mishra, Anjay Kumar (GS WOW: Wisdom of Worthy Research Journal, 2024)
This editorial examines the pivotal role of Madhesh University in addressing Nepal’s demographic challenges and fostering socioeconomic growth through innovative educational and research initiatives. As the country stands at the crossroads of a demographic dividend, with its youth population at an all-time high, the editorial highlights the critical window of opportunity to harness this potential amidst the challenges of gender inequality, limited access to education and healthcare, and high migration. It focuses on how Madhesh University is leveraging technology, interdisciplinary research, and community engagement to tackle these socio-demographic issues, with special emphasis on the development of the Institute of Federalism, sustainability initiatives, and forward-thinking projects like the Unnath Tarai Abhiyan. Furthermore, it discusses the university’s innovative patent application for a technology-driven risk management solution, showcasing its commitment to integrating technology and education. The editorial concludes by reaffirming the university’s vital role in shaping a prosperous and sustainable